Теоретический подход к проблеме мотивации персоналом на железнодорожном транспорте - Яковенко, Валентина Григорьевна; Гриценко, Наталья Валерьевна; Куделя, Виктория Ивановна (НТУ "ХПИ", 2016)
Мотивация персонала является основным средством обеспечения оптимального использования ресурсов, мобилизации имеющегося кадрового потенциала предприятия. В статье рассмотрено понятие мотивации, определены ведущие мотивы работников и причины их слабой мотивации, а также выделены мероприятия, по улучшению системы мотивации труда на железнодорожном транспорте. Мотивация персонала в значительной степени определяет как непосредственно успех деятельности организации, так и развитие экономики в стране, уровень благосостояния людей, которые предопределяют актуальность и важность проблем мотивации персонала.

Motivation is a key means of ensuring optimal use of resources, mobilization of existing personnel potential of the enterprise. The article deals with the concept of motivation, determined the leading motives of workers and the reasons for their poor motivation, as well as isolated events, to improve the incentive system on the railways. Staff motivation largely determines how successful the organization itself, and economic development in the country, the welfare of the people who determine the relevance and importance of the problems of staff motivation. The motive of human activity is the satisfaction of their needs, which have a complex hierarchical structure, different in different individuals. To effectively motivate employees need to match the goals and organization. The basic measures to improve the incentive system on the railways. Bring that choosing a system of incentives, should take into account the needs and interests of workers. Selected incentives should encourage individual employeeor the labor collective as a whole with respect to achieving individual and common goals of the enterprise.
A theoretical approach to the problem of motivating staff in railway transport
Keywords: мотивация; персонал; управление; трудовые ресурсы; транспорт железнодорожный; motivation; staff; human resource; rail transport; management